Signal-based analysis of the dynamic behaviour of the system in inertia friction welding and its impact on part contact evolution. (December 2021) - Raimondi, Luca; Bennett, Christopher J.; Gameros, Andres; Axinte, Dragos
Graphical abstract: Highlights: An approach to calculate the equivalent pressure distribution at the weld interface. A methodology to convert the pressure distribution in equivalent process loads. Analysis of the rotordynamic behaviour of the system in process conditions. Non-axisymmetric loads were recognised as the main cause of runout during welding. Abstract: Inertia friction welding (IFW) is a process used to create joints with high geometrical accuracy and near net shape form. To cope with the complex phenomena occurring during welding, the majority of available studies have analysed the interaction of the workpieces to be joined under simplified conditions, in which the influence of machine assembly tolerances, spindle dynamics and system compliance have been neglected. Among the dimensional properties, the headstock-tailstock concentricity is particularly important to assess the conformity of the weld, for this reason, a novel approach was developed to investigate the physical causes behind the evolution of the radial misalignment between the two workpieces, conventionally referred to as radial runout. First an inverse approach to evaluate the equivalent pressure distribution at the weld interface and the equivalent process loads was implemented starting from the experimental data of radial runout, headstock angular speed and strain extracted with a custom monitoring system during a set of steel welds. The results showed a large variability of the pressure distribution in circumferential direction and non-axisymmetric load components in particular during the conditioning and burnoff phases. Then, the equivalent process loads were used as an input for a Timoshenko beam dynamic representation of the spindle. A good agreement between the model and the experimental data was observed with an average relative error in the radial runout of 0.085. From these results, it was possible to conclude that the lack of axisymmetry in the load components has to be attributed mainly to the misalignment between two workpieces, while the irregular runout to compliance of the system to the non-ideal process loads.